ANALYSIS OF WEB-BASED COLLEGE ENGLISH TEACHING FROM 2000 TO 2017 IN CHINA - Zhang, Baohuan (English Education:Journal of English Teaching and Research, 2020)
Based on 812 papers on web-based college English teaching published in Chinese journals from 2000 to 2017, this study adopted modern statistical methods to explore the spatio-temporal development of the research. The results revealed the research on web-based college English teaching started in 2000 and had been increasing from 2006 to 2011; however, scholars’ attention to it was on the decline after 2012. During the period of 2000 -2017, the average annual number of papers published in Chinese journals was up to 45 while that in core journal was only 4. Meanwhile, there were significantly spatial differences. The research on web-based college English teaching in China has mainly focused on eastern region, particularly, Beijing and Guangdong as two main research regions, its average annual number of papers issued in core journals accounted for 9.5% of the total amount of the country respectively. We can see many well-known experts in "double first-class" universities pay little attention to the research on web-based college English teaching and there are weak foundation and low faculty. In recent years, college English teaching has been closely related to internet, also, colleges and universities increasingly put more emphasis on the significant influence of network on college English teaching, and however, the research level of web-based college English teaching needs to be improved further from the perspective of the quality and quantity of the published papers.